Antiherpetic medication and incident dementia: Observational cohort studies in four countries. (19th March 2021) - Schnier, Christian; Janbek, Janet; Williams, Linda; Wilkinson, Tim; Laursen, Thomas M.; Waldemar, Gunhild; Richter, Hartmut; Kostev, Karel; Lathe, Richard; G Haas, Jürgen
Abstract: Background and purpose: Several epidemiological studies from Taiwan, all using the same data resource, found significant associations between herpes virus infection, antiherpetic medication, and subsequent dementia. We conducted a multicenter observational cohort study using health registry data from Wales, Germany, Scotland, and Denmark to investigate potential associations between antiherpetic medication and incident dementia, and also to comprehensively investigate such associations broken down according to medication type and dose, type of herpes virus, and dementia subtype. Methods: A total of 2.5 million individuals aged 65 years or more were followed up using linked electronic health records in four national observational cohort studies. Exposure and outcome were classified using coded data from primary and secondary care. Data were analyzed using survival analysis with time‐dependent covariates. Results: Results were heterogeneous, with a tendency toward decreased dementia risk in individuals exposed to antiherpetic medication. Associations were not affected by treatment number, herpes subtype, dementia subtype, or specific medication. In one cohort, individuals diagnosed with herpes but not exposed to antiherpetic medication were at higher dementia risk. Conclusions: Short‐term antiherpetic medication is not markedly associated with incident dementia. Because neither dementia subtype nor herpes subtype modified the association, the small but significant decrease in dementia incidence with antiherpetic administration may reflect confounding and misclassification. Abstract : We conducted a multicenter observational cohort study using health registry data from Wales, Germany, Scotland, and Denmark to investigate potential associations between antiherpetic medication and incident dementia, broken down according to medication type and dose, type of herpes virus, and dementia subtype. Our results were heterogeneous, with a tendency toward decreased dementia risk in individuals exposed to antiherpetic medication. We conclude that short‐term antiherpetic medication is not markedly associated with incident dementia.